(3fXe GdahGFO heHOi GdahGFOs - (3CMeO Hf Ydj GdefMhQis; (3GdebQj , CMeO Hf eMeO Hf CMeO Hf jMji GdJdeSGfj, CHh GdYHGS,J (B1041 (3g` s
(3ChdgG (B:s
,(3HYO aGdZQV ef gPG GdehVY TQM bUjOI GdTjN GdEeGe GdYdGeI CHh GdYHGS CMeO Hf eMeO Hf RcQjG GdeYQha HGdJdeSGfi s
(3BNQgG (B:s
(3hgfG EfbVi gPG GdeNJUQ hGdMeO dQH GdYGdejf s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B237 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B78s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds